Effects of governance on the Environmental Kuznets Curve in South and South East Asian Countries - Gill, Abid Rashid (2017)
The objective of this study is to examine whether the better governance can minimise the environmental loss of economic growth at early stages of economic development.For this purpose, this study investigates the impact of governance indicators on the slope of the Environmental Kuznets Curve (EKC) in 19 countries of South and South East Asia for the period 2002-2015.The empirical output of the study reveals that five out of six indicators of governance have a strong impact on the slope of the EKC. Therefore, we conclude that environmental damages of economic growth can be minimised by strengthening the government institutions, rule of law and ensuring the transparency and accountability.